Assessment of halotolerant bacterial and fungal consortia for augmentation of wheat in saline soils - Marghoob, Muhammad Usama; Nawaz, Aniqa; Ahmad, Muhammad; Waheed, Muhammad Qandeel; Khan, Muhammad Hassaan; Imtiaz, Muhammad; Islam, Ejaz ul; Imran, Asma; Mubeen, Fathia (Frontiers in Microbiology, 2023)
Adaptations of green technologies to encounter abiotic stress including salinity for crops like wheat by using halotolerant microbes is a promising approach. Current study investigated 17 salt-affected agroecological zones from Punjab and Sindh provinces of Pakistan to explore the potential of indigenous microbial flora, with multiple biochemical characteristics, in addition to plant growth promoting (PGP) traits for enhanced wheat production in saline areas. Initially, 297 isolated pure bacterial colonies were screened for salt tolerance, biochemical, and PGP traits. Three bacterial strains belonging to Pantoea spp. and Erwinia rhaphontici with possession of multiple characteristics were selected for the development of halotolerant bacterial consortium. Inoculation of two local wheat varieties; Faisalabad 2008 and Galaxy 2013 with the consortium for in-vitro seed germination assay and sand microcosm experiments exhibited significant improvement in selected plant growth parameters like germination percentage and root structure. Two previously reported PGP fungal strains of Trichoderma harzianum and T. viridae were also used as fungal consortium separately for pot experiment and field trials. Pot experiment exhibited a positive correlation of consortia with metabolic viz; catalase, peroxidase, and proline and agronomical parameters including shoot length, dry weight, number of spikes, spike length, and 100 grain weight. To evaluate their performance under natural environmental conditions, field trials were conducted at three salt-affected sites. Agronomical attributes including days of flowering and maturity, flag leaf weight, length and width, shoot length, number of spikes, spike length, spike weight, number of seeds spike -1 , 1000 grain weight, and plot yield indicated the efficiency of these microbes to enhance wheat growth. Concisely, bacterial consortium showed better performance and Faisalabad 2008 was more resistant variety as compared to Galaxy 2013. Initial promising results indicate that further extensive research on indigenous microbes might lead to the development of the country's first saline-specific biofertilizers and sustainable eco-friendly agriculture practices.